Synthesis and Characterization of new Schiff base Ligand type [N4O4] from 3-(Ethoxymethylene)pentane-2.4-dione and its Niп Complex - Alsalihi, Eman I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
The Schiff base reaction plays an important role in the condensation reaction between 3-(ethoxymethylene) pentane- 2.4-dione and 3,3’-diaminobenzidine in the presence of calculated amounts of KOH as a catalyst. This reaction has been carried out in the ethanol under reflux and overnight stirring condition. All syntheses were carried out under an atmosphere of hydrogen forming a new ligand [3,3’,3’’,3’’’-(1E,1’E,1’’E,1’’’E)-(biphenyl-3,3’,4,4’-tetrayltetrakis (azan-1-yl-1-ylidene)) tetrakis (methan-1- yl-1-ylidene) tetrakis (4-methoxybut-3-en-2-one)] type [N4O4]. The ligand and its Niп complex of the general formula [Ni2(L)] have been characterized by spectroscopic methods (Fourier transform infrared and ultraviolet-visible), elemental analysis (C.H.N), metal content, magnetic susceptibility measurement, thin-layer chromatography, mass spectrometry, X-ray powder diffraction powder diffraction, 1H-nuclear magnetic resonance, molar conductance, and biological activity. The ligand and its Ni complex were exposed to two types of bacteria (Staphylococcus aureus and Bacillus subtilis), using the agar disc diffusion method, and the ligand and its Niп complex exhibited significant activities against these two types of bacteria. Our study revealed the formation of a new ligand type [N4O4] and four-coordinate tetrahedral structure around Niп metal ion with the ratio of 1:2 (ligand:metal) stable compounds which can be used in many fields, such as medicine and industry.